Caracterização mecânica de misturas asfálticas confeccionadas com agregados sintéticos de argila calcinada quanto a deformação permanente - Nunes, Fábio Roberto Garcia (2006)
This dissertation is focused in obtaining parameters to describe the process of permanent deformation in asphalt mixtures, specifically asphalt mixtures containing some synthetic clay aggregate (SCA's). An existing viscoplastic continuum damage model was used. The model takes into account several factors that influence the process of permanent deformation at high temperatures in these materials. Among them, the load or displacement rate dependency, confining pressure dependency, dilation, aggregate friction, aggregate interlockingand damage. The model is based on Perzyna’s theory of viscoplasticity with Drucker-Prager yield function modified to account the effect of damage. The model was used to describe the mechanical behavior of four asphalt mixtures made with SCA obtained from three different places from the state of Amazonas. The experiment was performed to systematically determine the model parameters and the evolution laws that describe asphalt mixes hardening and softening. The experimet consisted of a set of compressive triaxial strength tests conducted at three displacement rates and three confining pressures. Two displacement rates were used for obtaining the model parameters while a thirdrate was used to verify the obtained parameters. The existing model has shown potential to, satisfactorily capture the experimental results.